Post-Exercise Cardiac Troponin Release is Related to Exercise Training History - Mehta, R.; Gaze, D.; Mohan, S.; Williams, K. L.; Sprung, V.; George, K.; Jeffries, R.; Hudson, Z.; Perry, M.; Shave, R. (International Journal of Sports Medicine, 2012)
Marathon running can increase circulating cardiac troponin above the diagnostic criteria for myocardial infarction. We determined whether prior-exercise experience (training history) might be related to the magnitude of immediate post-race troponin release following completion of the London Marathon in a group of non-elite runners. Using a prospective study design, 52 runners were recruited into either HIGH T-E (trained-experience) (n=27) or LOW T-E (n=25) groups. Cardiac troponin I (cTnI) release following race completion was compared between these 2 groups. To examine relationships between cTnI release and participant demographic and indices of prior training experience an additional 52 runners who did not meet the criteria for either the HIGH T-E or LOW T-E groups were also recruited. The combined data from all 104 runners was analysed using multivariate linear regression analysis. The results revealed a significant difference in post marathon circulating cTnI between LOW T-E runners (median: 0.11 µg/L; interquartile range [IQR]: 0.03–0.18 µg/L) and HIGH T-E runners (median: 0.03 µg/L; IQR 0.02–0.057 µg/L) (p<0.05). Average miles run per week in the last 3 years, a marker of total training experience, encompassing training volume and duration, was negatively associated with post-marathon cTnI release (p<0.001).In conclusion, exercise-induced cTnI release is strongly related to previous training experience.
Keywords: marathon; training; cardiac damage